Isolation, phenotypic characterization and genome wide analysis of a Chlamydomonas reinhardtii strain naturally modified under laboratory conditions: towards enhanced microalgal biomass and lipid production for biofuels - Shin, Sung-Eun (Biotechnol Biofuels, 2017)
BACKGROUND: Microalgal strain development through genetic engineering has received much attention as a way to improve the traits of microalgae suitable for biofuel production. However, there are still some limitations in application of genetically modified organisms. In this regard, there has been recent interest in the isolation and characterization of superior strains naturally modified and/or adapted under a certain condition and on the interpretation of phenotypic changes through the whole genome sequencing. RESULTS: In this study, we isolated and characterized a novel derivative of C. reinhardtii, whose phenotypic traits diverged significantly from its ancestral strain, C. reinhardtii CC-124. This strain, designated as CC-124H, displayed cell population containing increased numbers of larger cells, which resulted in an increased biomass productivity compared to its ancestor CC-124. CC-124H was further compared with the CC-124 wild-type strain which underwent long-term storage under low light condition, designated as CC-124L. In an effort to evaluate the potential of CC-124H for biofuel production, we also found that CC-124H accumulated 116 and 66% greater lipids than that of the CC-124L, after 4 days under nitrogen and sulfur depleted conditions, respectively. Taken together, our results revealed that CC-124H had significantly increased fatty acid methyl ester (FAME) yields that were 2.66 and 1.98 times higher than that of the CC-124L at 4 days after the onset of cultivation under N and S depleted conditions, respectively, and these higher FAME yields were still maintained by day 8. We next analyzed single nucleotide polymorphisms (SNPs) and insertion/deletions (indels) based on the whole genome sequencing. The result revealed that of the 44 CDS region alterations, 34 resulted in non-synonymous substitutions within 33 genes which may mostly be involved in cell cycle, division or proliferation. CONCLUSION: Our phenotypic analysis, which emphasized lipid productivity, clearly revealed that CC-124H had a dramatically enhanced biomass and lipid content compared to the CC-124L. Moreover, SNPs and indels analysis enabled us to identify 34 of non-synonymous substitutions which may result in phenotypic changes of CC-124H. All of these results suggest that the concept of adaptive evolution combined with genome wide analysis can be applied to microalgal strain development for biofuel production. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13068-017-1000-0) contains supplementary material, which is available to authorized users.